Marketing and Branding Strategies for MSMEs Post-Pandemic, Especially in Rural Areas - Oriza Aditia; Dwi Febri Syawaludin; Mar'atus Solikhah (Politeknik Siber Cerdika Internasional, 2025)
The COVID-19 pandemic has provided impact significant to Micro , Small, and Medium Enterprises (MSMEs) sector , especially those in rural areas . Dependence on marketing traditional become challenge big moment mobility restricted . Post-pandemic , the emergence of habit consumer new as well as acceleration digitalization open opportunity at a time challenge in developing adaptive marketing and branding strategies . Research This aim For identify and analyze effective marketing and branding strategies for MSMEs in rural areas after pandemic , as well as explore factors determinant the success of the strategy in increase Power competitiveness and sustainability business . Research This use approach qualitative with studies cases of five MSMEs in rural areas West Java . Data collected through interview in-depth , observation direct , and documentation . The data analysis technique uses the Miles and Huberman model with stages data reduction , data display, and retrieval conclusion / verification . Research results show that a combination of simple digital strategies ( such as use of WhatsApp Business and social media local ), personalization product based wisdom local , as well as visual storytelling becomes key in building strong branding . Adoption technology in a way gradual , digital training , and collaboration with community local participate push the effectiveness of MSME marketing strategies post-pandemic .